Literature review: drivers of migration. Why do people leave their homes? Is there an easy answer? A structured overview of migratory determinants - Jana Kuhnt (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
Why do people leave their homes? This seemingly easy question requires a more complex answer. What ultimately prompts a person to leave if it is impossible to find a job due to a conflict that has destroyed all economic opportunities? Evidence suggests that the migration decision is a complex process that is dependent on a multitude of factors, such as migration governance regimes, migration and smuggler networks, access to technology, or individual characteristics such as age, gender and educational background. I use a theoretical framework to present the variety of determinants that have been put forward as influencing migration decisions at the macro-, meso-, and micro-level. This structured overview discusses their importance for different forms of migration and subsequently helps to identify gaps for further research.
Keywords: 320